Evaluation of an interprofessional naloxone didactic and skills session with medical residents and physician assistant learners - Hargraves D; White CC; Mauger MR; Puthota A; Pallerla H; Wigle P; Brubaker SL; Schlaudecker JD (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: The CDC has reported 399,230 opioid-related deaths from 1999-2017. In 2018, the US surgeon general issued a public health advisory, advising all Americans to carry naloxone. Studies show that enhanced naloxone access directly reduces death from opioid overdose. Despite this, health care professional learners report low knowledge and confidence surrounding naloxone. Therefore, it becomes critical that medical education programs incorporate didactic and experiential sessions improving knowledge, skills and attitudes regarding harm reduction through naloxone. Objectives: 1. Describe the components and evaluation of a replicable and adaptable naloxone didactic and skills session model for medical providers; 2. Report the results of the evaluation from a pilot session with family medicine residents and physician assistant students; and 3. Share the session toolkit, including evaluation surveys and list of materials used. Methods: In July 2017, a literature search was completed for naloxone skill training examining best practices on instruction and evaluation. A training session for family medicine residents and physician assistant learners was designed and led by University of Cincinnati College of Medicine and College of Pharmacy faculty. The same faculty designed a pre and post session evaluation form through internal review on elements targeting naloxone knowledge, attitude, and self-efficacy. Results: The training session included one hour for a didactic and one hour for small group live skills demonstration in four methods of naloxone administration (syringe and ampule, nasal atomizer, branded nasal spray and auto injector). Forty-eight participants showed statistically significant (p<0.05) improvement in knowledge (67.5% to 95.9%), attitudes (71.2% to 91.2%), and self-efficacy (62.1% to 97.8%) from pre to post assessment. Forty-four of 48 participants agreed that the pace of the training was appropriate and that the information will be of use in their respective primary care practices. Supply costs for the session were USD 1,200, with the majority being reusable on subsequent trainings. Conclusions: Our study of a naloxone didactic and skills session for primary care trainees demonstrated significant improvements in knowledge, self-efficacy, and attitudes. It provides an adaptable and efficient model for delivery of knowledge and skills in naloxone administration training. The pilot data suggest that the training was efficacious.